Palaeoceanographic evolution of the SW Svalbard shelf over the last 14 000 years. (18th September 2017) - Telesiński, Maciej M.; Przytarska, Joanna E.; Sternal, Beata; Forwick, Matthias; Szczuciński, Witold; Łącka, Magdalena; Zajączkowski, Marek
Abstract : The palaeoceanographic evolution of the SW Svalbard shelf west of Hornsund over the last 14 000 years was reconstructed using benthic foraminiferal assemblages, stable oxygen and carbon isotopes, and grain‐size and ice‐rafted debris data. The results reveal the complexity of the feedbacks influencing the shelf environment: the inflow of Atlantic and Arctic waters (AW and ArW, respectively), and the influence of sea ice and tidewater glaciers. The inflow of subsurface AW onto the shelf gradually increased with the first major intrusion at the end of the Bølling‐Allerød. During the Younger Dryas, the shelf was affected by fresh water originating from sea ice and glacier discharge. Glaciomarine conditions prevailed until the earliest Holocene with the intense deliveries of icebergs and meltwater from retreating glaciers and the occasional penetration of AW onto the shelf. Other major intrusions of AW occurred before and after the Preboreal oscillation (early Holocene), which resulted in more dynamic and open‐water conditions. Between 10.5 and 9.7 cal. ka BP, the shelf environment transformed from glaciomarine to open marine conditions. Between c.  9.7 and 6.1 cal. ka BP the AW advection reached its maximum, resulting in a highly dynamic and productive environment. At c.  6.1 cal. ka BP, the inflow of AW onto the Svalbard shelf decreased due to the intensification of the Greenland Gyre and the subduction of AW under the sea‐ice‐bearing ArW. Bioproductivity decreased over the next c.  5500 years. During the Little Ice Age, bioproductivity increased due to favourable conditions in the marginal sea‐ice zone despite the effects of cooling. The renewed advection of AW after AD 1850 started the climate warming trend observed presently. Our findings show that δ 18 O can be used to reconstruct the dominances of different water‐masses and, with some caution, as a proxy for the presence of sea ice in frontal areas over the northwestern Eurasian shelves.